Математические модели многоканальных инверторов с улучшенным спектральным составом выходного напряжения - Волков, И.В.; Каршенов, Д.П. (Технічна електродинаміка, 2015)
С помощью аналитического метода получены расчетные формулы, связывающие выход и вход инвертора, представляющие собой расчетную модель схемы замещения, состоящей из источников основной и высших гармоник напряжения. С помощью полученных математических моделей многоканальных инверторов оптимизированы схемные решения, наиболее полно удовлетворяющие требованиям электромагнитной совместимости этого класса устройств. Аналітичним методом отримано універсальні розрахункові формули, які зв'язують вихід і вхід інвертора, що є
розрахунковою моделлю схеми заміщення, яка складається з джерел вищих гармонік напруги. За допомогою
отриманих математичних моделей інверторів синтезовано технічні рішення, що найповніше задовольняють
вимогам електромагнітної сумісності цього класу пристроїв. The analytical method of estimation of inverter output voltage harmonics is developed. The universal formulas that describe
equivalent circuit of inverter are obtained .These formulas give a possibility to calculate the optimal commutation angles of
inverter semiconductors switches that provide the minimal Total Harmonic Distortion of multichannel inverters as function
of channel number and characteristics of power supply. The formulas can be used as for 3- phase systems with neutral, so
without neutral. Two types of power supplies are analyzed: with constant voltage and with pulsed one (supplying by rectifier).
The developed mathematical models permit to design powerful multichannel inverters with demanded electromagnetic
compatibility with another power electronic devices connected to common main.